AKUNTANSI USAHA DAGANG TOKO EMAS MODEL MANIS PALARAN SAMARINDA - Anita, Anita Anita (EKONOMIA, 2017)
Implementation of accounting at trading companies, specially in the Gold Storeâ€œModel Manisâ€ brand at Palaran, Samarinda Indonesian is very important and must exist, because accounting is a key indicator of business performance and is a tool for companies in decision making so as to improve the management of the company, through the application of good accounting, know how the development and health of his business, how much profit earned his business in a certain period. This is very important for business owners to assess the exact performance and health of their business. This study research to find out whether the business accounting of Gold Store â€œModel Manisâ€ brand at Palaran Samarinda Indonesian, already in accordance with the Financial Accounting Standards For Entities Without Public Accountability (SAK ETAP).Basic theory in this research is financial accounting, data used in this research are primary data and secondary data. Primary data is data obtained directly from the owner of The Gold Store â€œModel Manisâ€ brand at Samarinda city through interview. Secondary data is data obtained from the Gold Store â€œModel Manisâ€ Palaran Samarinda. The analytical tool used in this study using the formula Dean J. Champion.The result of the research shows that the accounting on the merchandise business of The Gold Store â€œModel Manisâ€ brand of Palaran Samarinda is quite in accordance with the Financial Accounting Standards For Entities Without Public Accountability (SAK ETAP), it can be seen from the calculation result using Dean J. Champion formula that is obtained 52% is located at 51% - 75%, although quite in accordance with SAK ETAP, but there are some things that need to be improved in the application of business accounting Gold Store â€œModel Manisâ€ brand of Palaran Samarinda Indonesian, which is necessary to reporting balance sheet and cash flow statement. This is so that the application of accounting is really in accordance with the Financial Accounting Standards For Entity Without Public Accountability (SAK ETAP).